Pelatihan Penggunaan Media Pembelajaran Berbasis Permainan (Digital Game Bassed Learning) Menggunakan Aplikasi Kahoot bagi Guru Madrasah MIN 3 Langkat - Enda Lovita Pandiangan; Khairat Umami; Muhammad Riski (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2024)
Digital based game learning is a medium that contains educational content that is translated into games with the aim of involving students. Digital game based learning utilizes learning through learning patterns and playing using a computer or smartphone. Through this media, students are stimulated by three things at once, namely emotional intelligence, cognitive intelligence and psychomotor skills. This community service activity aims to improve the skills of participants, namely MIN 3 Langkat teachers, in using digital teaching media based on game learning. Implementation of community service is carried out through several stages such as Pre-Survey, Formation of a PKM Team, Making Proposals, Coordinating Teams and Partners, Preparing Training Tools & Materials, Implementing training, evaluating. The number of participants was around 25 MIN 3 Langkat teachers. They feel they have gained insights and skills that are applicable and useful. After attending the training, all participants who initially did not know and could not use the Kahoot application became aware and even 44% of the 25 participants were able to use the Kahoot application well.